Corporate Social Responsibility Disclosures and Sustainable Financial Performance of Listed Oil and Gas Companies in Nigeria - Emovon, Felix Osayabor; Ogbonmwan, Evelyn Ehizogie (The Journal of Accounting and Management, 2025)
Objective: This research examines the effect of aspects of corporate social responsibility disclosure on the performance of publicly traded oil and gas companies in Nigeria. It investigates the extent to which disclosures related to waste management, greenhouse gas emissions, and staff welfare impact performance. Prior Work shows that companies that disclose their CSR practices are more positioned for better performance. However, there are others that contradict this assertion. This paper explores the impact of CSR disclosure on sustainable financial performance in Nigeria. Approach: An ex post facto research design was adopted. Focus was on eight oil and gas firms publicly traded on the Nigerian Exchange Group (NGX) as at 31/12/2023. Data were collected from their financial statements from 2014 to 2023 and analysed using panel regression analysis. Results indicate that waste management disclosures and greenhouse gas emissions negative and statistically insignificant, whereas employee welfare disclosure was positive and statistically significant. Implications and Value: The findings from this study has implication for employers in the oil and gas companies in Nigeria to increase their disclosure on employee welfare. It also extends existing knowledge by providing empirical evidence for other aspects of CSR disclosures which could be relevant to researchers.